2020
DOI: 10.1007/s42860-020-00098-2
|View full text |Cite
|
Sign up to set email alerts
|

Organo-Modification of Montmorillonite

Abstract: Modification of the surfaces of montmorillonite (Mnt) by organic molecules is an effective method for improving their affinity toward non-aqueous substances, and has resulted in extensive industrial applications as rheological control agents, drilling fluids, and other functional materials used in applications ranging from environmental remediation to coatings. The present study reviewed recent progress in organo-modification of Mnt, and provides state-of-the-art insights into proposed modification mechanisms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(19 citation statements)
references
References 140 publications
0
14
0
Order By: Relevance
“…Various organic chemicals have been applied in clays in efforts to enhance their efficiency, and the interactions between them have been studied (Li et al, 2019;Tan et al, 2019;Guo et al, 2020;Shen et al, 2020;Zhang et al, 2020). One of the most important chemical admixtures, polycarboxylate superplasticizers (PCEs), is a type of clay-sensitive superplasticizer.…”
mentioning
confidence: 99%
“…Various organic chemicals have been applied in clays in efforts to enhance their efficiency, and the interactions between them have been studied (Li et al, 2019;Tan et al, 2019;Guo et al, 2020;Shen et al, 2020;Zhang et al, 2020). One of the most important chemical admixtures, polycarboxylate superplasticizers (PCEs), is a type of clay-sensitive superplasticizer.…”
mentioning
confidence: 99%
“…Studies have shown that the structural characteristics of organically modified bentonite (OMB) are related to factors such as the type, concentration, dosage, and ratio of cationic surfactants [21]. By changing the dosage and ratio of surfactants and bentonite, the arrangement of organic molecules in the interlayer domain can be effectively controlled [22]. In the present research, the universally used organic cations for modification are quaternary ammonium salt cations with long alkyl chains, where cetyltrimethylammonium bromide (CTAB) surfactant is one of the most commonly used organic modifiers for bentonite [23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…In order to prepare nano-dispersed montmorillonite nanocomposites, it is necessary to organically modify the natural montmorillonite to enhance its compatibility with the resin matrix. It is one of the most widely used methods to improve the compatibility between montmorillonite and the polymer using cationic quaternary alkyl ammonium or alkyl phosphine to exchange the original metal cations such as Na + or Ca 2+ between the layers, which can expand the spacing between the layers of montmorillonite, realize the organic surface of the lamellar, and improve the affinity with the organic matrix [12][13][14][15]. However, the amino group in the cationic organic modifier affects the thermal stability of cationic organic montmorillonite (OMMT), which is difficult to meet the thermal stability and flameretardant performance requirements of polymer/montmorillonite composites.…”
Section: Introductionmentioning
confidence: 99%